Remodeling of Rat M. Gastrocnemius Medialis During Recovery From Aponeurotomy - Rivares, Cintia; Brunner, Reinald; Pel, Johan J. M.; Baan, Guus C.; Huijing, Peter A.; Jaspers, Richard T. (Frontiers in Physiology, 2020)
Aponeurotomy is a surgical intervention by which the aponeurosis is transsected perpendicularly to its longitudinal direction, halfway along its length. This surgical principle of aponeurotomy has been applied also to intramuscular lengthening and fibrotomia. In clinics, this intervention is performed in patients with cerebral palsy in order to lengthen or weaken spastic and/or short muscles. If the aponeurotomy is performed on the proximal aponeurosis, as is the case in the present study, muscle fibers located distally from the aponeurosis gap that develops lose their myotendinous connection to the origin. During recovery from this intervention, new connective (scar) tissue repairs the gap in the aponeurosis, as well as within the muscle belly. As a consequence, the aponeurosis is longer during and after recovery. In addition, the new connective tissue is more compliant than regular aponeurosis material. The aim of this study was to investigate changes in muscle geometry and adaptation of the number of sarcomeres in series after recovery from aponeurotomy of the proximal gastrocnemius medialis (GM) aponeurosis, as well as to relate these results to possible changes in the muscle length-force characteristics. Aponeurotomy was performed on the proximal aponeurosis of rat muscle GM and followed by 6 weeks of recovery. Results were compared to muscles of a control group and those of a sham-operated group. After recovery from aponeurotomy, proximal and distal muscle fiber lengths were similar to that of the control group. The mean sarcomere length from fibers located proximally relative to the aponeurosis gap remained unchanged. In contrast, fibers located distally showed 16–20% lower mean sarcomere lengths at different muscle lengths. The number of sarcomeres in series within the proximal as well as distal muscle fibers was unchanged. After recovery, muscle length-force characteristics were similar to those of the control group. A reversal of proximal-distal difference of fibers mean sarcomere lengths within muscles during recovery from aponeurotomy is hypothesized to be responsible for the lack of an effect. These results indicate that after recovery from aponeurotomy, geometrical adaptations preserved the muscle function. Moreover, it seems that the generally accepted rules of adaptation of serial sarcomere numbers are not applicable in this situation.